(untitled) (International Journal of Engineering and Computer Science, 2017)
The semantic web promises to bring automation to the areas of web service discovery, composition and invocation. It purports to take the Web to unexplored efficiencies and provide a flexible approach for promoting all types of activities in tomorrow’s Web. In this paper, we had proposed an ontology-based framework for composition of Web services. The model is also based on an iterative and incremental scheme meant to better capture requirements in accordance with service consumers’ needs. OWL-S markup vocabularies and associated inference mechanism are used and extended as a means to bring semantics to service requests. This framework is used for exploring interesting Compositions of existing Web services. In this approach we look for similarities between Web services and this method is followed if we are unaware of specific goal for services. The framework first screens web services for composition leads based on their service operations